Efficient and Low-Cost Metal Revision Techniques for Post Silicon Repair - Lee, Sungchul; Shin, Hyunchul (Journal of semiconductor technology and science, 2014)
New effective techniques to repair “small” design errors in integrated circuits are presented. As semiconductor chip complexity increases and the design period becomes tight, errors frequently remain in a fabricated chip making revisions required. Full mask revision significantly increases the cost and time-to-market. However, since many “small” errors can be repaired by modifying several connections among the circuit blocks and spare cells, errors can frequently be repaired by revising metal layers. Metal only revision takes significantly less time and involves less cost when compared to full mask revision, since mask revision costs multi-million dollars while metal revision costs tens of thousand dollars. In our research, new techniques are developed to further reduce the number of metal layers to be revised. Specifically, we partition the circuit blocks with higher error probabilities and extend the terminals of the signals crossing the partition boundaries to the preselected metal repair layers. Our partitioning and pin extension to repair layers can significantly improve the repairability by revising only the metal repair layers. Since pin extension may increase delay slightly, this method can be used for non-timing-critical parts of circuits. Experimental results by using academia and industrial circuits show that the revision of the two metal layers can repair many “small” errors at low-cost and with short revision time. On the average, when 11.64% of the spare cell area and 24.72% of the extended pins are added to the original circuits, 83.74% of the single errors (and 72.22% of the double errors) can be corrected by using two metal revision. We also suggest methods to use our repair techniques with normal commercial vender tools. KCI Citation Count: 0